Research of the frequency response parameters of antenna module circuit of the high frequency heating system of KTM tokamak plasma - Satibekov, A.N.; Kusainov, A.T.; Kulan, J.; Sarsembayev, Ye.A.; Chektybayev, B.J.; Gulkin, A.V. (Recent Contributions to Physics, 2022)
The article presents the results of measuring the parameters of the amplitude-frequency characteristics (AFC) of the antenna module circuit of the system for additional high frequency (HF) heating of the KTM tokamak plasma in laboratory conditions. A description of the antenna-feeder device and the HF system of the KTM tokamak is presented. At this stage of time, commissioning works for launching of the HF system of additional heating are performed at the KTM tokamak. The design and launch of such system requires conducting of separate research. Since the HF system consists of four modules, which includes various subsystems and components, before testing the entire HF system as an assembly, it is necessary to check and determine the parameters of individual components of the HF system. The antenna module is a part of the antenna-feeder device and is a very important component in the HF system, because it transfers energy from the generator to the tokamak plasma, thus heating the plasma. In case if the transmitting system does not match the declared operating frequency, HF system will be mismatched, which will affect the efficiency of plasma heating and operation of the entire HF system. It is impossible to bring the KTM tokamak to the nominal declared power without putting into operation of the system for additional HF heating of the plasma. Additional components are attached to the antenna module, the influence of which must also be studied for the correct operation of the entire HF system in the future. This paper presents a method for measuring the frequency response of the antenna module and the results of determining the operating parameters of the antenna module such as: wave impedance, inductance, capacitance, resonant frequency and quality factor of the antenna module circuit, depending on various additional inductance adjustment elements.